ANALYSIS OF LOVE DESIRE REFLECTED IN “FIRST LOVE”POEM BY JOHN CLARE - Setyo, Furiandanu (LANTERN (Journal on English Language, Culture and Literature), 2015)
The writer discusses love desire in poem of John Clare entitled “First Love”. The purpose of this study is to understand the poem through analyzing intrinsic and extrinsic elements of the poem. The methods used were library research and structural approach. By using the method of library research, the writer collects some information and document that support the process of analysis. The structural approach used by the writer to discover and analyze intrinsic element inside the poem. The extrinsic element analysis discusses about love desire in this poem by using theory of love by Erich Fromm. The result of the study shows how deep the poet’s love desire and consistency of loving her are, although the girl does not love him.